Syzygium polyanthum Leaf Ethanol Extract Accelerates Incision Wound Healing in Streptozotocin-Induced Diabetic Rats and Modulates NF-κB, iNOS and MMP-1 - Mei Jayanti Siregar; Endy Juli Anto; Jekson Martiar Siahaan (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
Diabetes mellitus (DM) significantly impairs wound healing through disruption of the inflammatory response and tissue metabolism. This study aimed to analyze the effect of ethanol extract of bay leaf (Syzygium polyanthum (Wight) Walp.) on NF-κB, iNOS, MMP-1, and wound healing in streptozotocin (STZ)-induced diabetic rats with incision wounds. A true experimental laboratory study with a post-test randomized controlled group design was conducted. Thirty male Wistar rats (n=5/group) were divided into six groups: normal control, DM control (STZ 40 mg/kgBW), DM with metformin (9.0 mg/rat/day), and DM with S. polyanthum extract at doses of 4.5, 9.0, and 18.0 mg/rat/day (equivalent to 250, 500, and 1000 mg/day human doses). Diabetes was induced by intraperitoneal STZ injection; wound healing was assessed on days 0, 7, and 14. Serum NF-κB, iNOS, and MMP-1 were measured by ELISA on day 14. Phytochemical screening confirmed flavonoids, alkaloids, saponins, tannins, and phenols, with total flavonoid content of 5.18 ± 0.16 mg QE/g extract and total phenolic content of 67.54 ± 0.64 mg GAE/g extract. Extraction yield was 11.35%. No significant differences were observed in serum NF-κB (p=0.103), iNOS (p=0.263), or MMP-1 (p=0.108) on day 14. However, wound area was significantly reduced at day 7 [F(5,24)=4.82, p=0.004], with the 1000 mg/kgBW-equivalent dose showing wound closure comparable to metformin. Ethanol extract of S. polyanthum demonstrates dose-dependent potential for accelerating wound healing in diabetic conditions, particularly during the proliferation phase. Further studies with larger cohorts and tissue-level analyses are warranted.